(untitled) (Journal of Global Humanities and Social Sciences, 2025)
This paper makes theoretical analysis and practical discussion on foreign-related format contracts, and holds that the protection of consumers’ rights and interests in foreign-related format contracts develops slowly from the perspective of consumer protection. This paper intends to analyze the reasons why consumers are in a natural weak position from the contradiction arising from the legal application of foreign-related format contracts. Although the appearance of foreign-related format contracts is in line with the trend of economic development, and it can not be banned unreasonably, the success of consumer rights protection is the foundation for the continuous improvement of the economic situation. Therefore, while protecting consumers, the impact on foreign-related format contracts should have a positive value orientation that can give consideration to substantive justice and conflict justice, and implement the guiding principle of protecting the interests of the weak.